Generation of an enhancer-driven gene expression viral tool specific to dentate granule cell-types through direct hippocampal injection - Potenza, Maria Letizia; Blankvoort, Stefan; Carvalho, Miguel M.; Grimstvedt, Joachim S.; Di Maria, Valentina; Moan, Kristian; Nair, Rajeevkumar Raveendran; Flatset, Marcus S.; Zhang, Qiangwei; Thomas, Laurent F.; Pauzin, Francois P.; Da Silva Mazzarini Baldinotti, Rodolfo; et al. (Frontiers in Neuroscience, 2024)
Accurate investigations of neural circuitry require specific genetic access to individual circuit elements, i.e., the myriad neuronal cell-types in the brain. However, native promoters cannot achieve this because while most genes are expressed in the brain, few are expressed in a single neuronal cell-type. We recently used enhancers, the subcomponents of the transcriptional apparatus which tell promoters when and where to express, combined with heterologous minimal promoters to increase specificity of transgene expression, an approach we call Enhancer-Driven Gene Expression (EDGE). As we discuss, EDGE is a marked improvement in specificity over native promoters, but still requires careful anatomical analysis to avoid off-target effects. In this study we present a more complete set of genomic markers from the mouse brain and characterize a novel EDGE viral vector capable of specifically driving expression in distinct subtypes of hippocampal neurons, even though it can express in other cell-types elsewhere. The advent of cell-type specific viral tools in wild-type animals provides a powerful strategy for neural circuit investigation and holds promise for studies using animal models for which transgenic tools are not available.